Characterization and timing of gastrointestinal bleeding in continuous flow left ventricular assist device recipients. Issue 9 (September 2020) - Kapuria, Devika; Khumri, Taiyeb; Shamim, Shariq; Surana, Pallavi; Khan, Salman; Al-Khalisi, Nabil; Aggarwal, Sanjeev; Koh, Christopher; Chhabra, Rajiv
Abstract: Background and aims: Heart failure is one of the leading causes of morbidity and mortality in the United States. The advent of left ventricular assist devices (LVAD) has improved the survival and quality of life in patients with end stage heart failure. Gastrointestinal bleeding (GIb) remains one of the limitations of LVADs. Methods: A single center, retrospective review of records was performed for patients who underwent LVAD implantation between 2010 and 2015. All patients who survived more than 30 days were followed till March 2016 and are described below. Results: A total of 79 patients were included in the study. The rate of GIb was 34.1% (27 patients) with a mean time to bleed of 267 days. Older patients were more likely to bleed. Upper GI bleeding was the source of bleeding in 54% patients. Arteriovenous malformations (AVM) were the source of bleeding in 74% bleeders and 80% of these patients had de novo AVM formation. 14/27 (51%) patients had a re-bleeding event. Thrombotic events were 4.5 times more likely to occur in patients who also had a GI bleed. Conclusions: GI bleeding in LVAD patients is common with the source of bleeding more commonly being in the upper GI tract. GI bleeding may occur as early as 10 days post procedure, despite previous negative screening endoscopies. There is an increased risk of thrombotic events in patients who have experienced a GI bleed. Abstract : Cardiology; Cardiovascular System; Circulatory System; Digestive System; Hematological System; Internal Medicine; Left ventricular assist devices; small bowel bleeding; arteriovenous malformations; thrombotic events.